1995
DOI: 10.1074/jbc.270.9.4632
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Human Genomic Region Containing the H Blood Group α(1,2)Fucosyltransferase Gene and Two H Locus-related DNA Restriction Fragments

Abstract: We have used the human H blood group alpha(1,2)fucosyltransferase (FUT1) cDNA to screen chromosome 19 cosmid libraries in a search for the human Secretor (Se) blood group gene (FUT2). One cosmid has been isolated that contains two distinct segments that cross-hybridize with FUT1. We have assembled a 100-kilobase (kb) cosmid contig, localized to 19q13.3, encompassing FUT1 and the two FUT1-related sequences, termed Sec1 and Sec2, for Secretor candidate 1 and 2. Sec1 and Sec2 are separated by 12 kb and are 65.5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
128
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(137 citation statements)
references
References 45 publications
9
128
0
Order By: Relevance
“…Rouquier et al [13] have indicated that a 3.35-kb FUT2 transcript was detected in poly(A)-rich RNA from normal small intestine, colon and lung tissues. Transcripts of FUT2 with a similar size were detected by northern blot analysis of total RNA from ovarian cancer MCAS cells and colonic cancer WiDr cells but not from erythroleukemic HEL cells (Fig.…”
Section: Expression Of Fut2 and Secl In Several Tumor Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rouquier et al [13] have indicated that a 3.35-kb FUT2 transcript was detected in poly(A)-rich RNA from normal small intestine, colon and lung tissues. Transcripts of FUT2 with a similar size were detected by northern blot analysis of total RNA from ovarian cancer MCAS cells and colonic cancer WiDr cells but not from erythroleukemic HEL cells (Fig.…”
Section: Expression Of Fut2 and Secl In Several Tumor Cell Linesmentioning
confidence: 99%
“…FUTI, FUT2, and a FUT2 pseudogene (Secl) have been isolated [ll-131. The putative amino acid sequences of these genes share a high degree of similarity and these genes are located within a 100-kb region on chromosome 19q13.3 [13], suggesting they were generated by gene duplication from the same ancestor gene and subsequently diverged. However, the cDNA of FUT2 has not been examined.…”
mentioning
confidence: 99%
“…The H enzyme is responsible for the expression of the H antigen in tissues derived from mesoderm and ectoderm, such as erythrocytes and vascular endothelial cells, and the Se enzyme for the expression of the same antigen in tissues derived from endoderm, such as epithelial cells of the digestive tract and exocrine glands (Watkins, 1980;Oriol et al, 1981Oriol et al, , 1986. The H and Se genes, and the Sec1 pseudogene constitute a cluster on the long arm of human chromosome 19 (19q13.3), where H is telomeric (Ball et al, 1991;Rouquier et al, 1994Rouquier et al, , 1995ReguigneArnould et al, 1995ReguigneArnould et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The human ABO-Secretor locus (FUT2) is responsible for the production of ABO histoblood group substances in the gastrointestinal tract and secretions. Following the cloning of the FUT2 gene Rouquier et al 1995), analyses of FUT2 polymorphism have indicated the heterogeneity of FUT2 alleles and the ethnic specificity of both functional (Se) and non functional (se) alleles in various populations Koda et al 1996 ;Liu et al 1998Liu et al , 1999. The se%#) allele, which contains a nonsense mutation G428A and a further six base substitutions compared to the reference allele reported by Kelly et al (1995) (see Fig.…”
mentioning
confidence: 99%